Sexual Dysfunctions in Obese Women Before and After Bariatric Surgery - Pichlerova, Dita; Bob, Petr; Zmolikova, Jana; Herlesova, Jitka; Ptacek, Radek; Laker, Matthew K; Raboch, Jiri; Fait, Tomas; Weiss, Petr (Medical science monitor, 2019)
BACKGROUND Obesity and associated comorbidities increase the probability of sexual disorders. The present study evaluated sexual satisfaction levels in obese women prior to and following bariatric surgery, utilizing the validated Female Sexual Function Index (FSFI) to also evaluate the sexual satisfaction in obese and non-obese women. MATERIAL AND METHODS 60 obese women (mean initial BMI of 43.7±5.9 kg/m²; mean age of 41.7±10.8 years) were administered the questionnaire on sexual function (FSFI) preceding bariatric surgery (laparoscopic adjustable gastric banding, 22 women; gastric plication, 33 women; and biliopancreatic diversion, 5 women), 6 months and 12 months after the procedure, i.e., following substantial weight reduction (final mean BMI of 35.5±5.5 kg/m²). The control group comprised 60 non-obese women (mean BMI of 22.2±1.9kg/m²; mean age of 36.4±10.7 years). RESULTS Our findings indicate that baseline sexual function in the preoperative obese females was significantly lower than in non-obese women, with p<0.01 in each domain. Data gathered at the 6- and 12-month points following the procedure indicated no significant difference. Before the procedure, 31 obese subjects (51.6%) exceeded the cutoff for FSD, at the 6-month evaluation point, 17 women (39.5%) exceeded the cutoff, and at 12 months postoperatively, 18 subjects (41.9%) exceeded the cutoff, indicative of FSD. Among the non-obese controls, only 9 subjects (15%) exceeded the cutoff threshold. CONCLUSIONS These findings show that substantive weight reduction resulting from bariatric surgery results in reduced sexual dysfunction in female subjects.
Keywords: obezita; Surveys and Questionnaires; Bariatric Surgery; Sexual Dysfunction, Physiological; hmotnostní úbytek; Humans; lidé středního věku; orgasmus; Female; dospělí; sexuální dysfunkce fyziologická; komorbidita; lidé; průzkumy a dotazníky; Obesity, Morbid; Orgasm; Adult; ženské pohlaví; Comorbidity; Middle Aged; morbidní obezita; bariatrická chirurgie; Obesity; Weight Loss